Effect of management and age of ploughed out grass–clover on forage maize yield and residual soil nitrogen. (22nd August 2018) - Cougnon, M.; Van Den Berge, K.; D'Hose, T.; Clement, L.; Reheul, D.
Abstract: Forage maize ( Zea mays L.) is often grown year after year on the same land on many intensive dairy farms in north-west Europe. This results in agronomical problems such as weed resistance and decline of soil quality, which may be solved by ley-arable farming. In the current study, forage maize was grown at different nitrogen (N) fertilization levels for 3 years on permanent arable land and on temporary arable land after ploughing out different types of grass–clover swards. Swards differed in management (grazing or cutting) and age (temporary or permanent). Maize yield and soil residual mineral N content were measured after the maize harvest. There was no effect on maize yield of the management of ploughed-out grass–clover swards but a clear effect of the age of grass–clover swards. The N fertilizer replacement value (NFRV) of all ploughed grass–clover swards was >170 kg N/ha in the first year after ploughing. In the third year after ploughing, NFRV of the permanent sward still exceeded 200 kg N/ha, whereas that of the temporary swards decreased to 30 kg N/ha on average. Soil residual nitrate (NO3 − ) remained below the local, legal threshold of 90 kg NO3 − N/ha except for the ploughed-out permanent sward in the third year after ploughing (166 kg NO3 − N/ha). The current study highlights the potential of forage maize – ley rotations in saving fertilizer N. This is beneficial both for the environment and for the profitability of dairy production in north-western Europe.